"Phantom of Chinatown" - Rosen, Philip E., 1888-1951; Waggner, George, 1894-1984; Luke, Keye, 1904-1991; Monogram Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Monogram Pictures, 1940)
A San Francisco detective, James Lee Wong, investigates the death of a noted archeologist and the theft of an ancient scroll. The sixth and final film in the Detective Wong series.
Originally released as a motion picture in 1940.
Based on the "James Lee Wong" series in Collier's Magazine written by Hugh Wiley.
Keye Luke, Lotus Long, Grant Withers.
Cinematographer, Fred Jackman Jr.; editor, Jack Ogilvie; music, Edward Kay.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 25, 2015).
Keywords: Wong, Mr. (Fictitious character) -- Drama; Scrolls -- Drama; Film adaptations; Detective and mystery films; Feature films; Fiction films; Internet videos; Streaming video